Postmodernism Educational Philosophy (Curriculum Review, Learning Methods And The Role Of Teachers) - Nasir, Muhammad; Assya'bani, Ridhatullah; Noor, Irfan; Iqbal, Muhammad (The International Journal of Education Management and Sociology, 2024)
Postmodernism educational philosophy is a view that criticizes and challenges the values and principles of modernism in the context of education. This study aims to explain the impact of postmodernism educational philosophy on three main aspects, namely curriculum, learning methods, and the role of teachers. In terms of curriculum, the postmodernist approach emphasizes diversity and plurality. The curriculum is no longer based on grand narratives or objective truths, but rather adapts to local contexts and student diversity. Education is directed at understanding various perspectives and diverse cultural stories. Learning methods in the educational philosophy of postmodernism emphasize the active participation of students. The learning process is no longer linear or authoritarian; Instead, teachers act as facilitators who encourage discussion, collaboration, and critical thinking. Understanding concepts is emphasized more than simply the acceptance of information. The role of teachers in the context of postmodernism has undergone significant changes. The teacher is no longer a single source of knowledge, but rather a mediator and facilitator. Teachers are expected to understand student diversity, respond to changes in society, and create an inclusive learning environment. This study uses a descriptive-analytical method by detailing the main concepts of postmodernism educational philosophy and applying them to the context of the curriculum, learning methods, and the role of teachers. Through analysis, it can be concluded that the educational philosophy of postmodernism is actually modernism itself which is actually used to criticize modernism itself to provide a change in the educational paradigm, emphasizing flexibility, participation, and recognition of diversity. The implication is the need for adjustments in educational practices to respond to the dynamics of contemporary society and prepare students to interact with a complex and varied world.